RETRACTED: Classification system of risks of nature-use activities in Arctic coastal eco-socio-economic systems - Gogoberidze George; Rumiantceva Ekaterina; Efimenko Ekaterina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001